1976
DOI: 10.1159/000458904
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Energetic Metabolism of Rat Myocardium during Acclimation to High Altitude

Abstract: The results reported in this paper refer to the modifications of energetic equilibrium in the myocardium tissue, involved by altitude chronic hypoxia. Experiments have been done on adult rats (males and females) placed in the Jungfraujoch station, in the Alps, at 3,500 m. The obtained data were compared to control animals, bred in Geneva. On the first days of stay at high altitude, a significant fall of tissue energy charge, due to the non-modified enzyme levels in comparison with the controls, was observed. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…If LDH B gene is generally considered not to respond to low oxygen supply [Ebert et al, 1996], some studies have demonstrated that its transcription can be down‐regulated by hypoxia in retina [Buono and Lang, 1999]. On the opposite, earlier physiological studies using rats as a model have shown that LDH B activity in skeletal muscle and heart [Barrie and Harris, 1976; Vergnes and Moret, 1976] could be up‐regulated during chronic hypoxia. Rat LDH B gene promoter structure is poorly documented but in fish, it exhibits a putative hypoxia response element [Rees et al, 2001].…”
Section: Discussionmentioning
confidence: 79%
“…If LDH B gene is generally considered not to respond to low oxygen supply [Ebert et al, 1996], some studies have demonstrated that its transcription can be down‐regulated by hypoxia in retina [Buono and Lang, 1999]. On the opposite, earlier physiological studies using rats as a model have shown that LDH B activity in skeletal muscle and heart [Barrie and Harris, 1976; Vergnes and Moret, 1976] could be up‐regulated during chronic hypoxia. Rat LDH B gene promoter structure is poorly documented but in fish, it exhibits a putative hypoxia response element [Rees et al, 2001].…”
Section: Discussionmentioning
confidence: 79%